Double condenser pulsating heat pipe cooler. (5th November 2017) - Torresin, Daniele; Agostini, Francesco; Mularczyk, Adrian; Agostini, Bruno; Habert, Mathieu
Highlights: A newly designed pulsating heat pipe cooler (PHP) based on automotive technology is investigated. The PHP has two condenser areas, one above and one below the evaporator. Measurements were performed with the refrigerant fluid R245fa in three different orientations. The results show that the device is orientation-free with identical performance in all tested orientations. Abstract: A novel pulsating heat pipe cooler (PHP) based on automotive technology is presented. This technology uses numerous aluminum Multiport Extruded (MPE) tubes disposed in parallel to achieve the desired compactness. The sub-channels of the MPEs are connected in a serpentine manner by means of fluid distribution elements integrated in the two condenser manifolds. This configuration enables the oscillation of liquid slugs and elongated bubbles between the evaporator and the condenser areas. This power electronics cooling system with a double condenser area was experimentally characterized and the thermal performances measured with R245fa are presented in this paper. The influence of different parameters such as the heat load, fluid filling ratio and orientation are investigated. The results show that the device is orientation-free: the performance was identical in all orientations, vertical, horizontal and anti-vertical.